A New Prognostic Index PDPI for the Risk of Pneumonia Among Patients With Diabetes - Guo, Lingxi; Song, Yanyan; Li, Ni; Qin, Binbin; Hu, Bin; Yi, Huahua; Huang, Jingwen; Liu, Bing; Yu, Liping; Huang, Yi; Zhou, Min; Qu, Jieming (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Risk factors for the development of pneumonia among patients with diabetes mellitus are unclear. The aim of our study was to elucidate the potential risk factors and attempt to predict the probability of pneumonia based on the history of diabetes. Methods: We performed a population-based, prospective multicenter cohort study of 1,043 adult patients with diabetes in China during 2017–2019. Demographic information, comorbidities, or laboratory examinations were collected. Results: The study included 417 diabetic patients with pneumonia and 626 no-pneumonia-onset diabetic patients. The predictive risk factors were chosen on the basis of a multivariate logistic regression model to predict pneumonia among patients with diabetes including: male sex (odds ratio [OR]=1.72, 95% confidence interval [CI]: 1.27–2.33, p<0.001), age≥75 years (OR=2.31, 95% CI 1.61–3.31, p<0.001), body mass index<25 (OR=2.59, 95% CI: 1.92–3.50, p<0.001), chronic obstructive pulmonary disease (OR=6.58, 95% CI: 2.09–20.7, p=0.001), hypertension (OR=4.27, 95% CI: 3.12–5.85, p<0.001), coronary heart disease (OR=2.98, 95% CI: 1.61–5.52, p<0.001), renal failure (OR=1.82, 95% CI: 1.002–3.29, p=0.049), cancer (OR=3.57, 95% CI: 1.80–7.06, p<0.001), use of insulin (OR=2.28, 95% CI: 1.60–3.25, p<0.001), and hemoglobin A1c≥9% (OR=2.70, 95% CI: 1.89–3.85, p<0.001). A predictive nomogram was established. This model showed c-statistics of 0.811, sensitivity and specificity were 0.717 and 0.780 respectively under cut-off of 125 score. Conclusion: We designed a clinically predictive tool for assessing the risk of pneumonia among adult patients with diabetes. This tool stratifies patients into relevant risk categories and may provide a basis for individually-tailored intervention for the purpose of early prevention.